New types of localization methods for adrenocorticotropic hormone-dependent Cushing's syndrome. Issue 1 (January 2021) - Senanayake, Russell; Gillett, Daniel; MacFarlane, James; Van de Meulen, Merel; Powlson, Andrew; Koulouri, Olympia; Casey, Ruth; Bashari, Waiel; Gurnell, Mark
Abstract : The management of endogenous Cushing's syndrome (CS) typically involves two key steps: (i) confirmation of autonomous hypercortisolism and (ii) localization of the cause to guide treatment. Adrenocorticotropic hormone (ACTH)-dependent CS is most commonly due to a pituitary corticotrope tumor which may be so small as to evade detection on conventional magnetic resonance imaging (MRI). Although biochemical testing (e.g., corticotropin stimulation; dexamethasone suppression) can provide an indication of the likely origin of ACTH excess, bilateral inferior petrosal sinus catheterization offers greater accuracy to distinguish pituitary-driven CS [Cushing's Disease (CD)] from the ectopic ACTH syndrome [EAS, e.g., due to a bronchial or pancreatic neuroendocrine tumor (NET)]. In patients with CD, 40–50% may not have a pituitary adenoma (PA) readily visualized on standard clinical MRI. In these subjects, alternative MR sequences (e.g., dynamic, volumetric, fluid attenuation inversion recovery) and higher magnetic field strength (7T > 3T > 1.5T) may aid tumor localization but carry a risk of identifying coincidental (non-causative) pituitary lesions. Molecular imaging is therefore increasingly being deployed to detect small ACTH-secreting PA, with hybrid imaging [e.g., positron emission tomography (PET) combined with MRI] allowing precise anatomical localization of sites of radiotracer (e.g., 11 C-methionine) uptake. Similarly, small ACTH-secreting NETs, missed on initial cross-sectional imaging, may be detected using PET tracers targeting abnormal glucose metabolism (e.g., 18 F-fluorodeoxyglucose), somatostatin receptor (SSTR) expression (e.g., 68 Ga-DOTATATE), amine precursor (e.g., 18 F-DOPA) or amino acid (e.g., 11 C-methionine) uptake. Therefore, modern management of ACTH-dependent CS should ideally be undertaken in specialist centers which have an array of cross-sectional and functional imaging techniques at their disposal.